Ex Vivo–expanded Natural Killer Cells Demonstrate Robust Proliferation In Vivo in High-risk Relapsed Multiple Myeloma Patients. Issue 1 (January 2015) - Szmania, Susann; Lapteva, Natalia; Garg, Tarun; Greenway, Amy; Lingo, Joshuah; Nair, Bijay; Stone, Katie; Woods, Emily; Khan, Junaid; Stivers, Justin; Panozzo, Susan; Campana, Dario; et al.
Abstract : Highly activated/expanded natural killer (NK) cells can be generated by stimulation with the human leukocyte antigen-deficient cell line K562, genetically modified to express 41BB-ligand and membrane-bound interleukin (IL)15. We tested the safety, persistence, and activity of expanded NK cells generated from myeloma patients (auto-NK) or haploidentical family donors (allo-NK) in heavily pretreated patients with high-risk relapsing myeloma. The preparative regimen comprised bortezomib only or bortezomib and immunosuppression with cyclophosphamide, dexamethasone, and fludarabine. NK cells were shipped overnight either cryopreserved or fresh. In 8 patients, up to 1×10 8 NK cells/kg were infused on day 0 and followed by daily administrations of IL2. Significant in vivo expansion was observed only in the 5 patients receiving fresh products, peaking at or near day 7, with the highest NK-cell counts in 2 subjects who received cells produced in a high concentration of IL2 (500 U/mL). Seven days after infusion, donor NK cells comprised >90% of circulating leukocytes in fresh allo-NK cell recipients, and cytolytic activity against allogeneic myeloma targets was retained in vitro. Among the 7 evaluable patients, there were no serious adverse events that could be related to NK-cell infusion. One patient had a partial response and in another the tempo of disease progression decreased; neither patient required further therapy for 6 months. In the 5 remaining patients, disease progression was not affected by NK-cell infusion. In conclusion, infusion of large numbers of expanded NK cells was feasible and safe; infusing fresh cells was critical to their expansion in vivo. Abstract : Supplemental Digital Content is available in the text.